Serum Levels and Adipose Tissue Gene Expression of Cathelicidin Antimicrobial Peptide (CAMP) in Obesity and During Weight Loss - Hochberg, Alexandra; Patz, Marissa; Karrasch, Thomas; Schäffler, Andreas; Schmid, Andreas (Hormone and Metabolic Research, 2021)
CAMP (Cathelicidin antimicrobial peptide) is synthesized and secreted by adipocytes and involved in adipose tissue (AT) innate immune response and host defense of subcutaneous AT against Gram positive bacteria. Data on the regulation of CAMP in obesity and during weight loss are scarce and reference values do not exist. Serum CAMP levels (ELISA) and AT gene expression levels (quantitative real time PCR) were investigated in two large and longitudinal (12 months) cohorts of severely obese patients undergoing either a low calorie diet (LCD; n=79) or bariatric surgery (BS; n=156). The impact of metabolic factors on CAMP expression in vitro was investigated in differentiated 3T3-L1 adipocytes. CAMP serum levels significantly increased after BS but not during LCD. Females had lower CAMP serum levels and lower gene expression levels in subcutaneous AT. CAMP was positively correlated to unfavorable metabolic factors/adipokines and negatively to favorable factors/adipokines. CAMP gene expression was higher in subcutaneous than in visceral AT but serum CAMP levels were not correlated to levels of AT gene expression. While certain bile acids upregulated CAMP expression in vitro, high glucose/insulin as well as GLP-1 had an inhibitory effect. There exist gender-specific and AT compartment-specific effects on the regulation of CAMP gene expression. Weight loss induced by BS (but not by LCD) upregulated CAMP serum levels suggesting the involvement of weight loss-independent mechanisms in CAMP regulation such as bile acids, incretins and metabolic factors. CAMP might represent an adipokine at the interface between metabolism and innate immune response.
Keywords: Cathelicidin antimicrobial peptide; diet; bariatric surgery; adipose tissue; adipocyte